Del papel en blanco y negro al Do it yourself digital. La evolución de la prensa graffitera en Madrid - Celeste Martín-Juan (Cahiers de Civilisation Espagnole Contemporaine)
Madrid has witnessed, since the seventies, the socio-cultural transformation of Spanish society and the emergence of different urban cultures (Rock, Punk, Heavy, etc.). At the same time, the city has seen the emergence of a new independent press movement specialized in these new cultural movements, such as fanzines. However, this process of evolution within the written press was not limited to the period of the 1970s. This has continued to transform into styles and formats thanks to the technological advances produced at the end of the 20th century and the digital revolution of the 21st century. To observe this change, this article reviews the case of Madrid Graffiti as an example of a specialized independent press. This scene of muralism in Madrid, linked to Hip Hop culture as its branch of aesthetic expression, serves as a case study to observe the evolution of the Spanish specialized press: from the beginnings of the photocopied fanzine; going through the press of specialized stores; until the moment it hits the newsstands; and, finally, the impact of new digital formats.